Analisis Perbedaan Hasil Belajar Mata Pelajaran Fikih MI Dengan Menggunakan Metode Ceramah dan Teams Games Tournament - Raikhan Raikhan (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2018)
The background of this research was that the quality of student learning outcome wasthe responsibility of the teacher. The teachers often still use the lecture method, so students become bored, therefore there must be innovation in the use of the teaching methods in accordance with the character of students. Learning method is very important to be able to improve student’s understanding and enthusiasm in following lesson. Among Teams Games Tournament (TGT) method. Student’s motivation to study was also necessary to improve the quality of student learning outcome, with the high motivation to study, the student would be very easy to interact in the learning environment. The purposes of this research were: 1) To determine differences in student learning outcome that was taught by lectureand Teams Games Tournament (TGT) method. 2) To determine differences in learning outcome on students who have different motivation to learn. 3) To determine the interaction between learning method on students who have different motivation to learn on the results. This research was a 2×2 factorial experiment design. The subject of this study was students of Class IV MI Mambaul Ulum Dagan. How to capture the subject of this study was with cluster random sampling technique, were the class IV B as group lecture, and IV A Class I as a group TGT. Data collection technique used tests and questionnaires,the analysis technique used was the Two-Way ANOVA (Analysis OF Variance). The first hypothesis test results showed that there was difference in learning outcome of students who were taught by the lecture method and TGT method, obtained sig 0.022 <0.05. Learning outcome of students who were taught by lecture method, amounted to 75.68, and the learning outcome of students who were taught by TGT method, amounted to 82.48. The second hypothesis suggests there were differences in learning outcome of students who had different motivation to learn, gained sig. amounted to 0.000<0.05. The average value of student learning outcome that had motivation to learnhigh of 88.00, the average value of student learning outcome of students who had low motivation to learn of 71.88. The third hypothesis exist the interaction between learning method on students who had differentmotivation to learn of the student learning outcome,obtained sig. by 0042> 0.05.